Anus-rectum defects. - Salvador G. Carrillo Soriano; Ruperto Llanes Céspedes; Sara González Fernández; Jorge Valdés Rodríguez; Miguel González Sabín; Ana Luisa Rodríguez Fernández; Lidia López Martín (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2005)
Anorectal malformations are one of big causes of de intestinal obstruction in newborns. They constitute around 25% of digestive malformations. Have a frequency of 1 in 4000 born alive. They are more frequent in the male (1.4:1) and 40 to 70% of the patients have one or more associate anomalies. We presented the Good Clinical Practices Guideline for Anorectal malformations, approved by consensus in the 2nd National Good Clinical Practices Workshop in Pediatric Surgery (Manzanillo, Cuba, September 31 - October 3, 2002).